Social innovation networks and territorial dynamics - Merlin-Brogniart, Céline (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
Social innovation networks are increasingly recognized as key players in social innovation. Based on qualitative case-studies, this research analyses, through the dimensions of proximity, the Actor-Network Theory and collaborative innovation - the process by which networks develop social innovations with a public service aim and create territorial dynamics. The findings reveal two types of implementation strategies, which create social and institutional proximity. Innovation processes, although not exempt from controversies, provide a broad latitude for local actors to negotiate, to adapt and share common tools or to create ad hoc methods. Organizational and cognitive proximity ensure collaborative governance and creativity. Territorial innovation dynamics rely on existing resources but the creation of new interactions also shapes the territorial service offering.